All Hallows' Eve : 13 stories - Vande Velde, Vivian (Orlando, Fla. : Harcourt, 2006)
Presents thirteen tales of Halloween horrors, including ghosts, vampires, and pranks gone awry.
Come in and rest a spell -- MARIAN -- Morgan Roehmar's boys -- Only on All Hallows' Eve -- Cemetery field trip -- Best friends -- Pretending -- I want to thank you -- When and how -- When my parents come to visit -- Edward, lost and far from home -- My real mother -- Holding on.
Keywords: Halloween -- Juvenile fiction; Supernatural -- Juvenile fiction; Short stories, American; Horror fiction; Short stories